Analysis of the rate of working women’s acceptance of partner violence and cultural reflections in Cypriot society - Başak, Neşe; Bulut Serin, Nergüz (Frontiers in Psychology, 2023)
This case study aims to measure the level of acceptance of violence among women and couples and to reveal the level of acceptance within and outside the families of women who have participated in working life. The concepts of anger and violence, physical, sexual, psychological, emotional, and economic violence, which are the sub-components of violence, violence in dating and marital relations are examined separately according to Feminism and Social Learning Theory approaches. The Working Group was formed by applying questionnaires to 50 participants from the cities of Kyrenia, Güzelyurt, Lefke, Nicosia and Magusa and determining the 20 participants with the highest level of acceptance of violence. The 11 people who agreed to the study were interviewed for a Dec of one week and 5 sessions ranging from 20-30 minutes. It is observed that women who are subjected to violence have a deep sense of helplessness and accept their helplessness, as well as those women resort to various passive solutions, such as silence and avoiding attitudes that make their partner angrier. The sense of helplessness, as a result of chronic depression, makes it inevitable to experience suicide cases. This study will be particularly important in terms of revealing the levels of domestic and non-family violence exposure and acceptance of violence by women who have participated in working life.